"Should a country's leaders apologize for its past misdeeds?" : an analysis of the effects of both public apologies from a belgian official and perception of congolese victims' continued suffering on Belgians' representations of colonial action, support for reparation, and attitudes towards the Congolose - Lastrego, Simona (Fundación Infancia y Aprendizaje, 2010)
Se analizarán las condiciones que facilitan que un grupo reconozca los delitos llevados a cabo por este mismo grupo en el pasado. Este reconocimiento puede suponer una amenaza para la identidad social de los miembros que pueden provocar estrategias defensivas.